2013
DOI: 10.1002/mnfr.201300272
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic effect of equol, a daidzein derivative, in cultured L6 myocytes and ob/ob mice

Abstract: The hypoglycemic effect of equol is related to increased GLUT4 translocation to the plasma membrane via AMPK activation. In addition, equol suppresses the fasting blood glucose level and gene expression of hepatic enzymes related to glucose metabolism. These results strongly suggest that equol has antidiabetic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
(50 reference statements)
7
25
0
Order By: Relevance
“…Several studies have reported that antidiabetic natural compounds such as resveratrol and berberine can activate AMPK and that the AMPK activation is important for their antidiabetic action [4,5]. We have also demonstrated that activation of AMPK is involved in the stimulation of glucose uptake induced by natural polyphenols, such as genistein, piceatannol, aspalathin, daidzein, and equol, which improve hyperglycemia in type 2 diabetic model mice [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several studies have reported that antidiabetic natural compounds such as resveratrol and berberine can activate AMPK and that the AMPK activation is important for their antidiabetic action [4,5]. We have also demonstrated that activation of AMPK is involved in the stimulation of glucose uptake induced by natural polyphenols, such as genistein, piceatannol, aspalathin, daidzein, and equol, which improve hyperglycemia in type 2 diabetic model mice [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 68%
“…These changes in GS and PEPCK are considered to increase glucose supply to blood stream and hence induce rises in the blood glucose levels. Some phytochemicals such as aspalathin and equol reversed these changes in hepatic gene expression of GS and PEPCK; the decreased expression of hepatic GS and the increased expression of PEPCK in untreated ob/ob mice were normalized by the treatment of such phytochemicals, leading to reduction of glucose production in the liver of ob/ob mice. In contrast, the hepatic gene expression of GS in db/db mice was significantly increased like that of PEPCK in the current study, and nepodin further increased the expression of GS without affecting that of PEPCK (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…However, more recently attention has also been given to its metabolites, like desmethylangolensin (DMA), dihydrodaidzein (DHD), and cis‐4‐OH‐equol, which are formed by intestinal bacteria . Among the daidzein metabolites, equol has been known to be very effective in the regulation of T2D . Several animal and human studies have been conducted to investigate the antidiabetic action of daidzein and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that soy food has antidiabetic effects. Equol was recently found to have an antihyperglycemic effect in T2DM model mice (27) although its effect on b-cell function remains unclear. The soy isoflavone genistein has been proposed as an agent to protect b-cell function and to prevent b-cell injury (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%